2015
DOI: 10.1080/13803395.2015.1072498
|View full text |Cite
|
Sign up to set email alerts
|

Silent reading fluency: Implications for the assessment of adults with developmental dyslexia

Abstract: Our results strongly suggest that dyslexic readers are less capable of significantly improve their reading speed when they read silently. Thus SRF could be considered a suitable parameter for identifying older students and adults with impairment in reading. A broader investigation of the issues surrounding silent reading is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 23 publications
2
17
1
2
Order By: Relevance
“…Interestingly, pseudoword reading was found to be particularly important in distinguishing students with dyslexia from both typical readers and malingerers [ 5 ]. We also replicated the finding of Gagliano et al [ 43 ] that students with dyslexia are impaired in silent text reading, in addition to the more commonly assessed oral (word) reading skills. Furthermore, students with dyslexia in higher education performed worse than typical readers on VAS, in line with previous studies indicating that visual processing skills do appear to play a role in adult reading performance [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Interestingly, pseudoword reading was found to be particularly important in distinguishing students with dyslexia from both typical readers and malingerers [ 5 ]. We also replicated the finding of Gagliano et al [ 43 ] that students with dyslexia are impaired in silent text reading, in addition to the more commonly assessed oral (word) reading skills. Furthermore, students with dyslexia in higher education performed worse than typical readers on VAS, in line with previous studies indicating that visual processing skills do appear to play a role in adult reading performance [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 88%
“…Text reading time : Text reading speed was included as an additional task for reading performance. Participants were presented with a short text (404 words), that was designed for the purpose of this study based on a text reading task by Gagliano et al [ 43 ]. Participants were asked to read the text silently.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Developmental dyslexia is a persistent reading disorder characterized by inaccurate or slow and effortful reading but also by poor spelling (American Psychiatric Association, 2013). It is a lifelong impairment, as numerous symptoms of childhood dyslexia persist into adulthood, particularly deficits in phonological processing, decoding skills, word reading fluency, phonological short-term memory, and phonemic awareness (Cavalli et al, 2016; Gagliano et al, 2015; Martin et al, 2010; Milne, Nicholson, & Corballis, 2003; Swanson & Hsieh, 2009). Neuroimaging studies have confirmed the persistence of phonological deficits (for a review, see Richlan, Kronbichler, & Wimmer, 2011), and some results suggest that this cognitive deficit may arise from congenital dysfunction in certain cortical areas involved in phonology and reading (Pugh et al, 2000; Shaywitz et al, 1998; Shaywitz et al, 2003).…”
mentioning
confidence: 99%
“…Most remediation programs as well as diagnostic instruments have, however, been developed for younger students (e.g., Regtvoort, Zijlstra, & van der Leij, 2013; Snowling, 2013; Tijms, 2011) and little is known about suitable ways to support older students with dyslexia. For example, most studies towards interventions focus on basic literacy skills, whereas more advanced skills such as silent reading (Gagliano et al, 2015), foreign language learning and advanced spelling receive less attention. Also, self‐esteem and self‐efficacy (Burns, Poikkeus, & Aro, 2013), have been shown to play an important role, and may form a basis for additional interventions.…”
Section: Discussionmentioning
confidence: 99%